Learning from overrated mission-oriented innovation policies: Seven takeaways - Magnus Henrekson; Christian Sandström; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2023)
This paper integrates findings from several different case studies on Mission-Oriented Innovation Policies (MOIPs) and makes use of existing literature to briefly describe three other missions: The War on Cancer, homeownership in the United States, and the Swedish Million Program. Together with the analyses in the contributions in the volume Moonshots and the New Industrial Policy: Questioning the Mission Economy, seven takeaways regarding mission-oriented innovation policies are developed and described: 1) wicked problems cannot be solved through missions, 2) politicians and government agencies are not exempt from self-interest, 3) MOIPs are subject to rent seeking and mission capture, 4) policymakers lack information to design MOIPs efficiently, 5) MOIPs distort competition, 6) government support programs distort incentives and result in moral hazard, and 7) MOIPs ignore opportunity costs. These seven takeaways are illustrated using the cases described in this essay and in other contributions in the above-mentioned volume
Keywords: H50; L26; L52; O31; O38; P16; 330; Mission-oriented policies; Innovation policy; New industrial policy; Moonshots; Rent seeking; Public choice